Egyptology search for the tomb of Osiris : being the journal of Miss Emily Sands, November 1926 - Sands, Emily; Andrew, Ian P. 1962-.; Harris, Nick 1958-.; Ward, Helen 1962-. (Dorking, Surrey, [England] Templar Pub., 2004)
Purports to be the journal of Emily Sands during her travels in Egypt in 1926 to find the lost tomb of Osiris. Based on real Egyptology, each chapter covers a different place in Egypt. Who can resist the allure of ancient Egypt-and the thrill of uncovering mysteries that have lain hidden for thousands of yearsn Not the feisty Miss Emily Sands, who in 1926, four years after the discovery of King Tut's tomb, led an expedition up the Nile in search of the tomb of the god Osiris. Alas, Miss Sands and crew soon vanished into the desert, never to be seen again. But luckily, her keen observations live on in the form of a lovingly kept journal, full of drawings, photographs, booklets, foldout maps, postcards, and many other intriguing samples. Here are just a few of Egyptology's special features: an extravagantly gilded cover, featuring a raised Horus hawk pendant with three encrusted gems, a playable game of Senet-ancient Egyptian checkers-including board, pieces, original-style dice, and rules, a souvenir booklet showing how to read simple hieroglyphs, a scrap of textured "mummy cloth", a facsimile of the gilded mummy mask of King Tut, a gilded eye-of-Horus amulet with a "jewel" at the end. Rich with information about life in ancient Egypt and peppered with Miss Sands's lively narration, Egyptology concludes with a letter from the former Keeper of Antiquities at the British Museum, explaining which parts of this unique tale may be accepted as fact, which are guided by legend, and which reflect the author's delightful sense of fancy.
Keywords: Toy and movable books -- Specimens; Egypt -- Antiquities -- Juvenile literature; Egypt -- Description and travel -- Juvenile literature